Neurocysticercosis in Children at GMC, Charak Hospital, Pokhara - Shrestha, SP; Dhungana, S; Shrestha, AK (Journal of Chitwan Medical College, 2013)
Neurocysticercosis (NCC) is a common cause of seizure and major cause of neurological illness globally. It is one of the major causes of epilepsy in children. Fewer studies were done in the past regarding NCC in Nepal. However study on NCC in children in Gandaki Medical College (GMC), Charak Hospital is the first of its kind. 23 children with CT scanning of head that were consistent with NCC over a period of 18 months at GMC, Charak Hospital were included as study subjects. Although there are so many diagnostic tools including MRI, immunological and serological tests for the detection of NCC, CT scanning of the head was used for its diagnosis in this study. 17.3% of the study subjects were found to have suffered from NCC. Girls (60%) outnumbered boys (40%); it was more commonly seen in 10-15 years age group (47.83%). Three main clinical presentations were Seizure (100%), Headache (73.91%) and Vomiting (30.43%). Most of the cases had ring enhancing lesion at colloidal stage. All patients were treated with albendazole, dexamethasone and antiepileptic drugs (AED) and advised strongly to continue for the period of at least 2 years without failure. NCC should be considered and CT/MRI head must be performed in all children above 5 years of age presented as seizure, headache or vomiting where Taenia solium (TS) infestations are found endemic. DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8437 Journal of Chitwan Medical College Vol.3(2) 2013 20-23